Radioresistant Nasopharyngeal Carcinoma Cells Exhibited Decreased Cisplatin Sensitivity by Inducing SLC1A6 Expression - Hao, Wenwen; Wu, Lisha; Cao, Linhui; Yu, Jinxiu; Ning, Li; Wang, Jingshu; Lin, Xiaoping; Chen, Yanfeng (Frontiers in Pharmacology, 2021)
Cisplatin-based regimens commonly applied for nasopharyngeal carcinoma (NPC) patients receiving concurrent chemotherapy and radiation. The sensitivity of cisplatin is closely associated with the efficacy of radiation therapy. We have developed two types of radio-resistant NPC cell lines HONE1-IR, and CNE2-IR, and observed that these two radio-resistant NPC cells also exhibited reduced sensitivity to cisplatin. Subsequent RNA-sequence showed that SLC1A6 was upregulated in both HONE1-IR and CNE2-IR. Downregulation of the SLC1A6 gene could enhance the sensitivity to cisplatin of both HONE1-IR and CNE2-IR cells. Notably, the expression of SLC1A6 was induced by cisplatin treatment and correlated with poor prognosis in NPC patients. We demonstrated that SLC1A6 contributed to reducing cisplatin sensitivity in radio-resistant NPC cells by altering drug metabolism profiles and genes, which may provide a theoretical foundation for developing a novel therapeutic target for radio-resistant NPC cells exhibited low response to cisplatin.